2007
DOI: 10.1016/j.jmb.2007.03.038
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Substrate–Substrate Interaction Found in the Kinase Domain of the Bifunctional Enzyme, 6-Phosphofructo-2-kinase/Fructose-2,6-bisphosphatase

Abstract: To understand the molecular basis of a phosphoryl transfer reaction catalyzed by the 6-phosphofructo-2-kinase domain of the hypoxia-inducible bifunctional enzyme 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFKFB3), the crystal structures of PFKFB3AMPPCPfructose-6-phosphate and PFKFB3ADPphosphoenolpyruvate complexes were determined to 2.7 A and 2.25 A resolution, respectively. Kinetic studies on the wild-type and site-directed mutant proteins were carried out to confirm the structural observations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 48 publications
(77 reference statements)
3
25
0
Order By: Relevance
“…An | F o |−| F c | omit map enabled unambiguous placement of N4A into theFru-6-P binding pocket of the kinase domain of PFKFB3 (Figure 6A). The N4A located at the Fru-6-P pocket could be superimposed onto the Fru-6-P modeled in the structure of PFKFB3 in a ternary complex with AMPPCP and Fru-6-P (PDB code: 2DWP) [29]. This structure provides clear evidence, supporting the kinetic observations that N4A competes with Fru-6-P for the same binding pocket in PFKFB3 (Figure 6B, C, D).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…An | F o |−| F c | omit map enabled unambiguous placement of N4A into theFru-6-P binding pocket of the kinase domain of PFKFB3 (Figure 6A). The N4A located at the Fru-6-P pocket could be superimposed onto the Fru-6-P modeled in the structure of PFKFB3 in a ternary complex with AMPPCP and Fru-6-P (PDB code: 2DWP) [29]. This structure provides clear evidence, supporting the kinetic observations that N4A competes with Fru-6-P for the same binding pocket in PFKFB3 (Figure 6B, C, D).…”
Section: Resultssupporting
confidence: 65%
“…To facilitate this task, it was necessary to determine the molecular characteristics of N4A binding to PFKFB3 by crystallizing human PFKFB3 in the presence of N4A. We determined the structure of this complex to 2.4 Å resolution by a method of molecular replacement using the first PFKFB3 structure (PDB code: 2AXN) as a search model [29]. An | F o |−| F c | omit map enabled unambiguous placement of N4A into theFru-6-P binding pocket of the kinase domain of PFKFB3 (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6), it is not unreasonable to suggest that methylation of these arginine residues contributes to constitutive PFKFB3 stabilization in cancer cells. Second, previous studies showed that R133, another arginine residue proximal to methylated arginine residues (R131/134) on the same helix, is able to interact with fructose-6-phosphate (F-6-P), the substrate of PFKFB3 with the covalent bond45. The current observation that R131/134K mutant-transfected cells displayed lower PFKFB3 activity than the WT-transfected cells (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Using ligands already known to bind to the F-6-P site from crystallographic evidence, namely, F-6-P [27] , F-2,6-P 2 [27] , EDTA [20] , and PEP [27] , a pharmacophore model was built and used to screen the NCI diversity set via MOE's pharmacophore screening module (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%